A skeletal mechanism for flame inhibition by trimethylphosphate. Issue 2 (3rd March 2016) - Bolshova, Tatyana A.; Shvartsberg, Vladimir M.; Korobeinichev, Oleg P.; Shmakov, Andrey G.
Abstract : On the basis of a multi-step kinetic mechanism for flame inhibition by organophosphorus compounds including more than 200 reactions, a skeletal mechanism for flame inhibition by trimethylphosphate was developed. The mechanism consists of 22 irreversible elementary reactions, involving nine phosphorus-containing species. Selection of the crucial steps was performed by analysing P-element fluxes from species to species and by calculating net reaction rates of phosphorus-involving reactions versus the flames zone. The developed mechanism was validated by comparing the modelling results with the measured and simulated (using the starting initial mechanism) speed and the chemical structure of H2 /O2, CH4 /O2 and syngas/air flames doped with trimethylphosphate. The mechanism was shown to satisfactorily predict the speed of H2 /O2 /N2 flames with various dilution ratios, CH4 /air and syngas/air flames doped with trimethylphosphate. The skeletal mechanism was also shown to satisfactorily predict the spatial variation of H and OH radicals and the final phosphorus-containing products of the inhibitor combustion. Further reduction of the skeletal mechanism without modification of the rate constants recommended in the starting mechanism was shown to result in noticeable disagreement of the flame speed and structure.